Covenant, Mohar, and Shalom: A Contextual Theological Dialogue between Old Testament Marriage and Javanese Marriage Culture - Ana Budi Kristiani; Vian Klasia Wenno (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2026)
This study analyzes the theological and cultural dimensions of marriage by examining key Old Testament texts and their dialogical engagement with Javanese marriage practices. The unit of analysis includes selected biblical passages (Gen 2:18–24; Exod 22:16–17; Mal 2:13–16; Hos 1–3; Ruth 4) alongside core elements of Javanese rituals such as seserahan, panggih–sungkeman, and kenduri. The aim is to construct a contextual theological framework that critically integrates biblical concepts of covenant, economic responsibility, and communal joy with Javanese cultural values. This research employs a qualitative, literature-based method combining historical-grammatical exegesis, Ancient Near Eastern contextual analysis, and anthropological interpretation of Javanese culture. A comparative thematic approach is used to identify points of resonance and tension between the two traditions. The findings reveal three key insights. First, the covenantal nature of Old Testament marriage resonates with Javanese ideals of harmony (rukun) and relational fidelity. Second, the concept of mohar parallels seserahan as a cultural expression of responsibility and respect toward women, while requiring critical evaluation to avoid economic excess. Third, communal celebration in biblical wedding feasts aligns with kenduri as an expression of shared joy and social cohesion. This study contributes a contextual theological model that affirms cultural values while offering critical discernment, thereby enriching contemporary discussions on marriage, theology, and culture in non-Western contexts.